FAKTOR KONVERSI BETA•KAROTEN SAYURAN YANG DIKERINGKAN PADA TIKUS PERCOBAAN - Almasyhuri -; Erwin Affandi (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2006)
Background: The conversion value of ~-carotene to vitamin A is dependlng on the kind of foods. The ratio is about 11 : 1 for fruit and 31 : 1 for vegetable, but the conversion value of dried vegetables had not known yet. Objective: To determine the conversion value of carotene dried vegetable to vitamin A. Method: The study was conducted using 35 white mice strain KLMR (Lembaga Makanan Rakyat)", which bred in Center for Research and Development Nutrition and Food, Bogar. Thirty five mice were divided into the 5 groups: first group (I} was given low vitamin A feeding contained 1 μg vitamin A per gram; the groups 11, 111, IV and V were given food which contained ~-carotene 30 μg per gram from pure ~carotene, young cassava leaf, old cassava leaf, and carrot. Analysis of blood for vitamin A and ~-carotene before and after of study was done using HPLC (High Performance liquid Chromatography). Result: The study concluded that the conversion value of ji-carotene to vitamin A is 17: 1, the ~-carotene of young cassava leaf is 20 : 1 and carrot is 23 ; 1. [Penel Gizi Makan 2006, 29(2): 92-97)